Bandstand at Vauxhall Garden - Rowlandson, Thomas, 1756-1827 (artist):::Creator:::::::::::: (2022)
Color etching and aquatint of the bandstand at Vauxhall Garden in London depicting a band playing in a multi-tiered elaborately decorated pavilion while couples dance and mingle below. Extracted from The Microcosm of London.